2014
DOI: 10.1038/gt.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Ad5 precursor terminal protein accelerates recombinant adenovirus packaging and amplification in HEK-293 packaging cells

Abstract: Recombinant adenoviruses are one of the most common vehicles for efficient in vitro and in vivo gene deliveries. Here, we investigate whether exogenous precursor terminal protein (pTP) expression in 293 cells improves the efficiency of adenovirus packaging and amplification. We used a piggyBac transposon-based vector and engineered a stable 293 line that expresses high level of Ad5 pTP, designated as 293pTP. Using the AdBMP6-GLuc that expresses green fluorescent protein (GFP), BMP6 and Gaussia luciferase, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 49 publications
4
99
0
Order By: Relevance
“…293pTP cells were derived from HEK-293 cells and overexpression of human Ad5 pTP gene as previously characterized [50]. The cell lines are maintained in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gemini Bio-Products, West Sacramento, CA), containing 100 U/ml penicillin and 100 mg/ml streptomycin, at 37°C in 5% CO 2 as described [51-53].…”
Section: Methodsmentioning
confidence: 99%
“…293pTP cells were derived from HEK-293 cells and overexpression of human Ad5 pTP gene as previously characterized [50]. The cell lines are maintained in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gemini Bio-Products, West Sacramento, CA), containing 100 U/ml penicillin and 100 mg/ml streptomycin, at 37°C in 5% CO 2 as described [51-53].…”
Section: Methodsmentioning
confidence: 99%
“…The coding regions of Cre recombinase and firefly luciferase (FLuc) were PCR amplified and subcloned into an adenoviral shuttle vector and subsequently used to generate recombinant adenoviruses in our recently engineered packaging line 293pTP [57], resulting in adenoviruses Ad-Cre and Ad-FLuc, which also express GFP as a marker for monitoring infection efficiency. Analogous adenovirus only expressing GFP (Ad-GFP) was used as a control [44,58,59,60,61,62,63,64,65,66].…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that overexpression of human Ad5 pTP in HEK-293 cells can enhance the amplification and packaging of adenovirus [16]. However, the possible contributions of adenoviral genes, which are known to participate in viral gene expression and DNA replication, have not been comprehensively evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Adenoviral lysate samples were prepared in five-fold serial dilution and used to infect subconfluent HEK-293 cells seeded in 6-well cell culture plates as described [11, 16]. The numbers of GFP or RFP-positive cells were counted at 36-48h post infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation